2010
DOI: 10.2147/orr.s7741
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan: its potential application in intervertebral disc regeneration

Abstract: Hyaluronan (HA) is a ubiquitous component of extracellular matrix in human tissues with diverse functions in skeletal biology. The biophysical properties of HA, such as high viscosity, elasticity and highly negative charge, make it useful in various therapeutic procedures. Although intra-articular administration of HA has been extensively used in the management of osteoarthritis (OA), there is a paucity of data on the clinical application of HA in intervertebral disc repair. This review discusses the biology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Hyaluronic acid (HA) has been a popular choice as an injectable biomaterial for delivery to the NP region of the intervertebral disc, as HA is a key component of the native extracellular matrix. HA biomaterials have several advantages in that they are biocompatible with a long history of clinical use, non-immunogenic, and their side chains can be readily manipulated to present various functional groups [8, 2225]. Studies have demonstrated proof-of-concept for HA-based biomaterials, alone or in combination with a second constituent such as collagen, gelatin or poly(ethylene glycol), as cell carriers to the disc [14, 19, 2631].…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronic acid (HA) has been a popular choice as an injectable biomaterial for delivery to the NP region of the intervertebral disc, as HA is a key component of the native extracellular matrix. HA biomaterials have several advantages in that they are biocompatible with a long history of clinical use, non-immunogenic, and their side chains can be readily manipulated to present various functional groups [8, 2225]. Studies have demonstrated proof-of-concept for HA-based biomaterials, alone or in combination with a second constituent such as collagen, gelatin or poly(ethylene glycol), as cell carriers to the disc [14, 19, 2631].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the injection of genipin resulted in the integration of AF tissue in degenerated IVD temporarily and improved interfacial shear properties between the AF lamellae [ 60 , 61 , 62 , 63 ]. The application of different natural polymers (collagen, alginate, chitosan, silk, and hyaluronan) and synthetic biomaterials (lactic-glycolic composites, poly (1, 8-octanediol malate) and polycaprolactone) for the AF repair have been reported in several studies [ 64 , 65 , 66 , 67 , 68 , 69 ]. To fabricate collagen-based implants, collagen fibers have been harvested from animal tail tendons and were cross-linked in situ using riboflavin or ammonia [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Repair Strategies For the Annulus Fibrosusmentioning
confidence: 99%
“…Unique viscoelastic properties of HA enables it to maintain rheological homeostasis of the synovial fluid in the joints and plays a critical role in providing lubrication, elasticity, and shock absorption to joint tissues. Furthermore, by providing a coat on the surface of articular cartilage, HA protects the cartilage and blocks the loss of proteoglycan from the cartilage matrix into the synovial space [41]. In healthy joint of human knee, the normal concentration of HA in the synovial fluid is in the range of 2.5 -4.0 mg/mL.…”
Section: Hyaluronic Acid Derived Viscosupplementsmentioning
confidence: 99%